Non-fluorinated hybrid PAEK / silicone resin coating

By using a combination technology of a porous hard bottom layer and a silicone resin-based finish layer on cooking utensils, the shortcomings of existing coatings in terms of mechanical strength and wear resistance are solved, and high durability and non-stick properties are achieved in high temperature environments.

CN119604219APending Publication Date: 2025-03-11SEB SA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380056490.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-29
Filing Date
2023-07-28
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The coating of existing cooking utensils has shortcomings in terms of mechanical strength and wear resistance, especially when used in high temperature environments, the problem of reduced brittleness and non-stick properties is prone to occur.

Method used

The porous hard bottom layer consists of polyether aryl ketone (PEAK) and its mixture, and applied to it a silicone resin-based finish layer, the coating is prepared by thermal spraying and pneumatic spraying techniques, adding fillers such as alumina and silicon carbide to improve mechanical properties.

Benefits of technology

It significantly improves the scratch resistance and mechanical impact resistance of the coating, ensuring good non-stick properties and durability under high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005257582870000141
    Figure BDA0005257582870000141
  • Figure BDA0005257582870000151
    Figure BDA0005257582870000151
  • Figure BDA0005257582870000421
    Figure BDA0005257582870000421
Patent Text Reader

Abstract

The invention relates to a coated cooking element (1) for a kitchen appliance or an electric cooking appliance, comprising a metal substrate (2), from which at least the following layers are coated in said sequence on at least one face (2a): (3a) a porous hard base layer, (3b) optionally, one or more intermediate layers consisting of one or more polyether aryl ketones (PEAKs) and mixtures thereof, optionally a filler, optionally less than 3% by weight of an additive, relative to the weight of the hard base layer, and optionally less than 3% by weight of a colorant, relative to the weight of the hard base layer, (3b) optionally, one or more outer layers consisting of one or more polyether aryl ketones (PEAKs) and mixtures thereof, (3c) a coating layer consisting of one or more colorants and optionally one or more silicone resins and / or one or more thermoplastic polymers and / or one or more fillers and / or one or more additives, (3c) a finish layer comprising one or more colorants and optionally one or more silicone resins and / or one or more thermoplastic polymers and / or one or more fillers and / or one or more additives, the present invention relates to a composition consisting of one or more silicone resins and optionally one or more thermoplastic polymers and / or one or more fillers and / or one or more additives and / or flakes; the invention also discloses a method for manufacturing the cooking utensil and a kitchen utensil or cooking utensil comprising the cooking utensil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to cooking utensils having a coating applied on one surface thereof, and more particularly to silicone resin-based coatings for such utensils. Background Art

[0002] In the field of cookware, coatings based on fluoropolymers, in particular polytetrafluoroethylene (PTFE), are known for their non-stick and temperature-resistant properties.

[0003] However, these coatings have low mechanical strength.

[0004] Application WO2020 / 144051 relates to a fluoropolymer-based coating whose mechanical wear resistance is improved by introducing organic (SiC) and inorganic (Al2O3) fillers in the main layer and the finishing layer of the coating.

[0005] The performance improvement achieved in terms of mechanical strength is satisfactory, but still not optimal.

[0006] Fluoropolymer-based coatings are mainly used for pots and pans, but due to their stampability other applications are possible in the field of molding (moulds, cake pans, waffle makers, etc.) or small household appliances (rice cookers, deep fryer containers, electric pancake makers).

[0007] Alternatives to PTFE coatings include the use of so-called "ceramic" coatings, which were developed by the sol-gel process and using sodium orthosilicate (EP 2806776 B1). These coatings have the particular properties of being hard and resistant to mechanical wear, but also exhibit brittle behavior and lower non-stick properties compared to coatings based on fluoropolymers.

[0008] Furthermore, these coatings are not well suited for molding and small household devices due to their lack of stampability.

[0009] In the field of molding (molding by the general public or industry), fluoropolymer based coatings are not widely used because the temperature resistance limit is lower (up to 220°C) and allows the use of other types of coatings, such as silicone coatings.

[0010] Pure silicone resins are non-stick and can withstand temperatures above 220-230°C. In contrast, they are considered to have poor adhesion to substrates.

[0011] On the other hand, silicone polyester resins are very widely used for molding, since they are non-sticky when adhered to the substrate and are compatible with stamping processes. However, they degrade at temperatures above 230°C. More particularly, cooking utensils are used in the temperature range of 50-250°C, and it is not surprising that temperatures of 300°C or even 350°C are reached in the case of utensils with induction bottoms. Their use is therefore incompatible with the temperatures of use in the field of cooking utensils.

[0012] The object of the present invention is to improve the technical problem of the scratch and chip resistance of silicone coatings by preparing the bottom layer in contact with the metal substrate based on a mixture of thermoplastic and / or thermally stable polymers with high thermomechanical properties.

[0013] In order to significantly improve the scratch resistance of silicone coatings, the inventors have shown that it is possible to prepare a macroporous primer layer with a formulation of a hot melt resin suitable for spraying on a metal substrate by thermal spraying without preheating to more than 100° C., and then directly apply one or more layers of liquid silicone coating by conventional pneumatic spraying. Reinforcing fillers (aluminum oxide, silicon carbide, etc.) may also be present in the primer layer.

[0014] The preparation of this "composite" with the silicone firmly fixed in the matrix of the polymer base layer produces a final coating with greatly improved mechanical properties.

[0015] Due to the good cohesion between the PEEK base layer and the layers of the coating, the coating has excellent adhesion properties.

[0016] The present invention allows the manufacture of monolithic layers of high thickness without causing cracks and fissures.

[0017] It has excellent scratch resistance and mechanical shock resistance.

[0018] The invention makes it possible to obtain excellent anti-scratch properties while maintaining a process with a single final cure, which makes it industrially economical.

[0019] Scratch and impact resistance has been extensively improved, and using metal utensils will not cause major damage.

[0020] As a result, the consumer will have a more durable item with a coating that more effectively prevents direct food contact with the substrate (increased durability of non-stick properties, increased safety in case of contact with aluminum, improved aesthetics, etc.).

[0021] The process has no preheating or drying at elevated temperatures and only a single final cure at temperatures below 400°C. The process is inexpensive and durable.

[0022] Therefore, a coating that is stronger when faced with mechanical stress will also have increased durability in terms of non-stick, non-fouling and corrosion resistance properties.

[0023] Patent EP2319631 describes the development of a two-layer silicone resin-based coating (base layer) combined with 0.5 to 20% of a high-temperature thermoplastic material, making it possible to obtain a coating that is mechanically strong, adheres to the substrate and is non-sticky. The properties of the thermoplastic vary between the base layer (PEEK) and the facing layer (PPS), and it is mainly located in the base layer to ensure adhesion to the substrate. The patent does not describe a temperature indicator.

[0024] Application US 2022 / 0073785 proposes a two-layer silicone / thermoplastic coating structure, which is more concentrated in the thermoplastic material and also does not describe the introduction of color indicators based on thermochromic pigments. Summary of the invention

[0025] A first object of the invention relates to a coated cooking element (1) for a cooking utensil or electric cooking utensil, comprising a metal substrate (2) coated on at least one face (2a) with at least the following layers, in order starting from the metal substrate (2):

[0026] (3a) a porous hard substrate, which consists of one or more polyether aryl ketones (PEAK) and mixtures thereof, optionally fillers, optionally less than 3 wt. % additives relative to the weight of the hard substrate, and optionally less than 3 wt. % colorants relative to the weight of the hard substrate,

[0027] (3b) optionally one or more intermediate layers, said intermediate layers consisting of one or more colorants and optionally:

[0028] - one or more silicone resins, and / or

[0029] - one or more thermoplastic polymers, and / or

[0030] - one or more fillers, and / or

[0031] - One or more additives

[0032] (3c) a finishing layer, the finishing layer consisting of one or more silicone resins and optionally:

[0033] - one or more thermoplastic polymers, and / or

[0034] - one or more fillers, and / or

[0035] - one or more additives, and / or

[0036] - Thin flakes.

[0037] Another object of the present invention relates to a method for manufacturing a coated cooking element (1) according to the present invention, comprising the following successive steps:

[0038] a) providing a metal support (2) comprising two opposing surfaces;

[0039] b) optionally, a step of treating the face (2a) of the support (2) to obtain a treated face (2a) that promotes the adhesion of the hard bottom layer (3a) on the support (2);

[0040] c) a step of producing an adherent hard base layer (3a) on said inner face (2a) by thermally spraying onto said inner face (2a) a powder or dispersion of one or more polyether aryl ketones (PEAK) and mixtures thereof, optionally fillers, optionally less than 3% by weight of additives relative to the weight of said hard base layer (3a) and optionally less than 3% by weight of colorants;

[0041] d) optionally drying and / or curing;

[0042] e) optionally applying the one or more layers (3ab) and / or one or more intermediate layers (3b);

[0043] f) applying the finishing layer (3c);

[0044] g) drying and / or curing.

[0045] Another object of the present invention relates to a cooking utensil (100) comprising a coated cooking element (1) according to the present invention.

[0046] Another object of the present invention also relates to an electric cooking appliance (200) comprising a coated cooking element (1) according to the present invention and a heating source (210) designed to heat the coated cooking element (1).

[0047] definition

[0048] In the context of the present invention, the term "layer" should be understood as a continuous or discontinuous layer. A continuous layer (also called integral layer) is a single integral body forming the entire flat surface completely covering the surface to which it is applied.

[0049] The term "discontinuous" refers to a layer that is not uniform in thickness across the surface on which it is deposited. In some places there may be no coverage.

[0050] The terms "base layer", "primer layer", "adhesion layer" or "adhesion primer" shall mean all layers from the first layer applied directly to the carrier (preferably this layer adheres well to the carrier and contributes all its mechanical properties: hardness, scratch resistance) to the last layer before the first decorative layer.

[0051] The term "finish layer" or "finish" shall mean a continuous transparent surface layer which allows perfect visibility of the decorative layer while protecting it from mechanical attack and giving the coating non-stick properties.

[0052] Preferably, the final finishing layer is intended to come into contact with food.

[0053] The term "decoration" or "decorative layer" refers to one or more continuous or discontinuous layers comprising a pigment composition. The decoration may be in the form of one or more patterns having one or more colors. The decoration is clearly visible to the naked eye of the user and is clearly visible at the usual distances at which the household article is used.

[0054] The term "overlapping layers" shall refer to partially or fully overlapping layers. The layers may be in the form of partially overlapping patterns, such as concentric disks.

[0055] The term "adjacent layers" shall mean non-overlapping layers. The layers may be in non-overlapping, identical or different patterns, preferably uniformly distributed.

[0056] The term "reference temperature pigment composition" refers to a composition comprising a pigment which, at a given temperature, indicates to the user that the optimum use temperature has been reached. This indication is made by comparing the color of the thermochromic pigment composition with the color of the reference temperature pigment composition. Either the optimum use temperature is reached when the colors are identical, or the optimum use temperature is reached when the colors are visually very different.

[0057] A "reference temperature pigment composition" may comprise a pigment having the following characteristics:

[0058] - the same color as the thermochromic pigment composition at the optimum use temperature,

[0059] * or because the pigment at ambient temperature has the same color as the thermochromic pigment composition at the optimal use temperature and does not change color with temperature,

[0060] * or because the pigment has a different color at room temperature than a thermochromic pigment composition that becomes the same color as the thermochromic pigment composition at the optimal use temperature,

[0061] - A colour which is substantially different from the colour of the thermochromic pigment composition at the optimum use temperature, whether or not the pigment changes colour with changes in temperature.

[0062] The optimum use temperature is reached when the color of the reference temperature pigment composition corresponds to the color indicated in the user guide of the household article comprising the coating according to the invention or to the color indicated on a color scale provided to the user together with the article.

[0063] The reference temperature pigment composition is thermochromic or thermally stable.

[0064] The reference temperature pigment composition may be, for example, a reference cooking temperature pigment composition or used to indicate a risk of overheating.

[0065] The present invention has at least the following advantages:

[0066] - the coating according to the invention functions as a thermochromic with a pronounced visibility, contrasting color change in a targeted temperature range and focused around food cooking temperatures, e.g. in kitchen appliances;

[0067] - when cooking food, the coating according to the invention can provide good temperature control, which is necessary for health and taste reasons, but also for safety and to limit accidental overheating that could weaken the coating;

[0068] - the thermochromic pigment composition has reversible thermochromic properties, i.e. after a color change under the action of heat, the compound returns to its initial state and its initial color when the temperature is lowered; this color change cycle (reversibility) can be repeated indefinitely;

[0069] - The coating of the invention has remarkable thermal stability when the temperature is increased; it is stable up to about 450°C;

[0070] In the meaning of the present invention, the expression "thermochromic semiconductor" shall mean that it must include an inorganic or organic compound that has a reversible color change after an increase in temperature. The gradual and reversible thermochromic properties of these semiconductor compounds are related to the reduction of the width of the semiconductor band gap caused by the expansion of the material. More specifically, the periodicity of the network of anions and cations leads to the aggregation of energy levels into energy bands. The energy band filled with higher energy is called the valence band, and the empty energy band with lower energy is called the conduction band. Between these two bands, there is a forbidden band called the band gap. The color of semiconductor materials can come from the presence of charge transfer, which corresponds to the passage of electrons from the valence band to the conduction band on a given atom, or generally from the anion orbit to the cation orbit (interatomic photon absorption).

[0071] In the field of application of the invention, optimal conditions are obtained when the coating reaches a temperature suitable for cooking food, preferably between 100 and 250°C.

[0072] In the context of the present invention, the term "thermochromic pigment or pigment composition" is understood to mean a pigment or pigment composition that changes color with temperature within a given temperature range, and this change is reversible. This color change is visible to the user with the naked eye and at a normal use distance.

[0073] The term "heat-stable pigment" refers to a pigment that does not show a change in color when subjected to an increase in temperature within a given temperature range, or a pigment that shows a change in hue when subjected to an increase in temperature within a given temperature range, wherein the given temperature range is so small that it is not visible to the user with the naked eye and is not visible at normal usage distances.

[0074] Thermally stable pigments preferably have a color change ΔE* of less than 10 between 25°C and 200°C, ΔE* being defined in the CIELAB color space by the CIE 1976 formula:

[0075]

[0076] L1*, a1* and b1* characterize the L*a*b* values ​​of the compound at ambient temperature,

[0077] L2*, a2* and b2* characterize the L*a*b* values ​​of the compounds at 200°C.

[0078] The expression "same color" shall mean that they are indistinguishable by the user with the naked eye and at a distance of ordinary use.

[0079] In the context of the present invention, the expression "cooking utensil" is to be understood as a utensil used for cooking. For this purpose, it is intended to be subjected to a heat treatment.

[0080] In the context of the present invention, the expression "article for heat treatment" is to be understood as an article to be heated by an external heating system, such as frying pans, frying pans, woks, stir-fry pans and grills, and which is capable of transferring the heat provided by the external heating system to the material or food in contact with the article.

[0081] In the context of the present invention, the expression "electric cooking appliance" should be understood as a heating object having its own heating system, for example an electric pancake maker, an electric raclette appliance, an electric fondue appliance, an electric grill, an electric pancake grill, an electric rice cooker, a bread maker or an electric pressure cooker.

[0082] The term "coating" shall refer to all layers that adhere to the metal substrate and cover the substrate. The coating obtained according to the invention is advantageously solid. The term "solid" refers to the property of the binding material being insoluble in water, insoluble in conventional solvents, in food components such as aqueous or fatty mixtures, even though the material may have high hardness or high flexibility, such as elastomers.

[0083] The term "silicone resin-based coating" refers to a coating comprising one or more silicone resins in one or more layers thereof.

[0084] The term "equivalent diameter of a pore" refers to the diameter of a sphere having the same volume as the pore in question.

[0085] The term "average equivalent diameter of pores" shall mean the average value of the equivalent diameters of pores.

[0086] The term "median equivalent diameter of the pores" shall mean the median of the equivalent diameters of the pores: 50% of the pores have an equivalent diameter smaller than this diameter, 50% have a higher equivalent diameter.

[0087] In the present invention, weight % is expressed on a dry basis, ie without solvent. BRIEF DESCRIPTION OF THE DRAWINGS

[0088] [ Figure 1 ]: Schematic diagram of a cooking element according to the invention, wherein layer (3b) is continuous and covers the entire layer (3a).

[0089] [ Figure 2 ]: Schematic diagram of a cooking utensil according to the invention, wherein layer (3b) does not cover the entire layer (3a) and forms a decoration.

[0090] [ Figure 3 ]: Schematic diagram of a cooking element according to the invention, wherein the layer (3b) comprises two decorations (i) and (j).

[0091] [ Figure 4 ]: Pattern distribution diagram. 4A = non-overlapping adjacent patterns. 4B = partially overlapping patterns. 4C = overlapping patterns.

[0092] [ Figure 5 ]:SEM-EDXS analysis, Example 1.

[0093] [ Figure 6 ]:SEM-EDXS analysis, Example 2.

[0094] [ Figure 7 ]: X-ray microtomography analysis of Example 2.

[0095] [ Figure 8 ]: Illustration of a cooking appliance according to the present invention.

[0096] [ Fig. 9 ]: Illustration of an electric cooking appliance according to the present invention. DETAILED DESCRIPTION

[0097] The invention relates to a coated cooking element (1) for a cooking appliance or electric cooking utensil, comprising a metal substrate (2) which is coated on at least one face (2a) with at least the following layers, in order starting from the metal substrate (2):

[0098] (3a) a porous hard substrate, which consists of one or more polyether aryl ketones (PEAK) and mixtures thereof, optionally fillers, optionally less than 3 wt. % additives relative to the weight of the hard substrate, and optionally less than 3 wt. % colorants relative to the weight of the hard substrate,

[0099] (3b) optionally one or more, preferably two, intermediate layers consisting of one or more colorants and optionally:

[0100] - one or more silicone resins, and / or

[0101] - one or more thermoplastic polymers, and / or

[0102] - one or more fillers, and / or

[0103] - One or more additives

[0104] (3c) a finishing layer, the finishing layer consisting of one or more silicone resins and optionally:

[0105] - one or more thermoplastic polymers, and / or

[0106] - one or more fillers, and / or

[0107] - one or more additives, and / or

[0108] - Thin flakes.

[0109] Advantageously, the layer (3a) and the optional layers (3b) and (3c) form a coating (3) coating the metal substrate (2). The coating (3) has non-stick properties and forms a non-stick coating.

[0110] Advantageously, the layer ( 3 a ) is in contact via one of its faces with the metal substrate ( 2 ) via its face ( 2 a ).

[0111] Thus, at least one coated face (2a) of the metal substrate is a cooking face. In other words, the coating of the cooking element (1) according to the invention is intended to come into contact with food.

[0112] The coating of the cooking element (1) according to the invention does not contain fluorinated polymers, also called fluoropolymers. In other words, the coating is or is free of fluorinated polymers.

[0113] The coating of the cooking element (1) according to the invention does not contain any fluorinated polymers.

[0114] The coating of the cooking element (1) according to the invention is intended to come into contact with food.

[0115] Advantageously, the finishing layer (3c) is in contact with the food via one of its faces and thus forms the cooking surface (5).

[0116] Advantageously, the one or more polyaryletherketones (PAEK) are selected from the group consisting of polyetherketone (PEK), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetheretherketoneketone (PEEKK) and polyetherketoneetherketoneketone (PEKEKK), particularly preferably PEEK and mixtures thereof.

[0117] Preferably, the average thickness of the hard bottom layer (3a) is greater than 5 μm, more preferably greater than 15 μm, particularly preferably between 20 and 50 μm. The average is the average of at least 10, preferably 15, measurements of the thickness at, for example, 10 or 15 random locations.

[0118] Advantageously, the average equivalent diameter of the pores in the hard bottom layer (3a) is greater than 5 μm.

[0119] The porosity data of the hard bottom layer (3a), in particular the total porosity fraction, the average equivalent diameter of the pores and the median equivalent diameter of the pores, were measured by X-ray microtomography using a synchrotron source.

[0120] Preferably, the average equivalent diameter of the pores of the hard bottom layer (3a) is greater than 8 μm, more preferably greater than 10 μm.

[0121] Preferably, the median equivalent diameter of the pores of the hard sublayer (3a) is greater than 6 μm, more preferably greater than 7 μm, and even more preferably greater than 8 μm.

[0122] Preferably, in the hard bottom layer ( 3 a ), more than 30%, more preferably more than 40%, particularly preferably more than 50% by number of the pores have an average equivalent diameter of ≤10 μm.

[0123] Preferably, more than 20%, more preferably more than 30%, by number of the pores in the hard bottom layer (3a) have an average equivalent diameter >10 μm and ≤20 μm.

[0124] Preferably, more than 60%, more preferably more than 70%, particularly preferably more than 80% by number of the pores in the hard bottom layer (3a) have an average equivalent diameter of ≤20 μm.

[0125] Preferably, more than 5%, more preferably more than 7%, particularly preferably more than 10% by number of the pores in the hard bottom layer (3a) have an average equivalent diameter of >20 μm and ≤30 μm.

[0126] Preferably, the pores in the hard bottom layer (3a) have an equivalent pore diameter greater than 30 μm by number, preferably at least 1% by number of the pores in the hard bottom layer (3a) have an equivalent pore diameter greater than 30 μm.

[0127] Preferably, the hard bottom layer (3a) has a surface roughness Ra between 5 μm and 100 μm, more preferably between 10 μm and 60 μm.

[0128] Preferably, the developed surface area Sdr of the hard bottom layer (3a) is between 10% and 100%, preferably between 30% and 80%.

[0129] Advantageously, the thickness of the layer (3c) is between 0.05 μm and 100 μm, preferably between 0.08 μm and 20 μm, particularly preferably between 0.1 μm and 10 μm. In a specific embodiment of the invention, the thickness of the layer (3c) is 100 nm + / - 5 nm.

[0130] According to one embodiment, the thickness of the layer ( 3 c ) is between 0.1 μm and 2 μm, preferably between 0.2 μm and 1.5 μm.

[0131] According to a further embodiment, the thickness of the layer ( 3 c ) is between 10 μm and 100 μm, preferably between 20 μm and 85 μm, particularly preferably between 30 μm and 70 μm.

[0132] The coating of the cooking element (1) according to the invention may comprise one or more optional layers (3ab) interposed between the one or more layers (3a) and the one or more layers (3b) or between the one or more layers (3a) and the one or more layers (3c), and the one or more optional layers are composed of one or more silicone resins and optionally

[0133] - one or more thermoplastic polymers, and / or

[0134] - one or more fillers, and / or

[0135] - one or more additives,

[0136] Advantageously, when present, the thickness of the layer or layers ( 3ab ) is between 0.05 μm and 100 μm, preferably between 0.08 μm and 20 μm, particularly preferably between 0.1 μm and 10 μm.

[0137] Advantageously, the thickness of the layer ( 3 b ) is between 1 μm and 100 μm, preferably between 2 μm and 30 μm, particularly preferably between 3 μm and 10 μm.

[0138] Metal substrate

[0139] Advantageously, the metal substrate (2), also called carrier, is a substrate made of aluminum, stainless steel, cast iron or aluminum, iron, titanium or copper.

[0140] Within the meaning of the present invention, aluminum is understood to be a metal consisting of 100% aluminum or an aluminum alloy.

[0141] Advantageously, the metal substrate (2) is a substrate made of aluminum, stainless steel or a multilayer metal substrate. The metal substrate (2) can be a two-layer or three-layer substrate, these multiple layers can be obtained by, for example, co-lamination, by thermal diffusion under load (solid state bonding) or by thermal or cold shock bonding.

[0142] Preferably, the metal substrate (2) comprises alternating layers of metals and / or metal alloys.

[0143] According to one embodiment, the metal substrate (2) is a substrate made of aluminum or a stainless steel alloy, or is a multi-layer metal substrate whose surface (2a) is aluminum or a stainless steel alloy.

[0144] Preferably, the metal substrate (2) is an aluminum substrate.

[0145] Advantageously, the thickness of the metal substrate (2) is between 0.5 mm and 10 mm.

[0146] Advantageously, the face (2a) of the metal substrate (2) has undergone a previous surface treatment in order to improve the adhesion of the coating to said substrate.

[0147] According to one embodiment, the surface of the face (2a) of the metal substrate (2) has undergone a surface treatment which is chemical etching, brushing, hydration, sandblasting, shot blasting, physicochemical plasma, corona or laser treatment, chemical activation or a combination of these different techniques.

[0148] Advantageously, the face (2a) of the substrate on which the coating (3) according to the invention is to be applied can be treated to increase its specific surface area; for aluminium substrates, this treatment can be carried out by anodising (producing a tubular aluminium oxide structure), by chemical etching, sandblasting, brushing, shot peening or by adding material using techniques such as thermal spraying (flame, plasma or arc spraying). Other metal substrates can also receive the addition of material by polishing, sandblasting, brushing, micro-bead blasting or using techniques such as thermal spraying (flame, plasma or arc spraying).

[0149] Metal substrates that can be used in the present invention advantageously include substrates made of aluminum, which may or may not be anodized, optionally polished, brushed, sandblasted, shot blasted or micro-bead blasted, substrates made of aluminum alloys, which may or may not be anodized, optionally polished, brushed, sandblasted or micro-bead blasted, substrates made of steel, which may optionally be polished, brushed, sandblasted, shot blasted or micro-bead blasted, substrates made of stainless steel, which may optionally be polished, brushed, sandblasted or micro-bead blasted, substrates made of cast steel, aluminum or iron, and substrates made of copper, which may optionally be hammered or polished.

[0150] Advantageously, the substrate may be selected from a substrate comprising a ferritic stainless steel / aluminium / austenitic stainless steel layer, a substrate comprising a stainless steel / aluminium / copper / aluminium / austenitic stainless steel layer, cast aluminium, an aluminium or aluminium alloy cap lined with a stainless steel outer base, a metal co-laminated substrate, such as a two-layer co-laminated substrate comprising a stainless steel layer (e.g. for constituting the inner surface of the article) and an anodised or non-anodised aluminium or aluminium alloy layer (e.g. for constituting the outer surface of the article).

[0151] Advantageously, the surface of the face (2a) of the metal substrate (2) has an arithmetic mean roughness Ra greater than or equal to 1 μm.

[0152] The arithmetic mean roughness Ra is measured by a roughness meter according to standard ISO 4287. Ra denotes the arithmetic mean of the deviations from the mean. The surface topography can be studied, in particular using a profilometer with a probe equipped with a fine pen with a diamond tip or with a The surface topography data can be used to determine the arithmetic mean roughness Ra.

[0153] Silicone resin

[0154] In the body of the description, the expression "silicone resin" is used interchangeably to refer to silicone before or after it has been crosslinked. In the body of the description, the expression "silicone" refers to an organopolysiloxane material. Crosslinking is a step that makes it possible to transform the silicone into an insoluble material, for example by polyaddition, polycondensation or dehydrogenation. The crosslinking is carried out on a precursor, generally an oil or a silicone resin, which crosslinks to obtain a three-dimensional network, forming the material referred to in the description as silicone resin.

[0155] This crosslinking can be performed by thermal activation or chemical activation using a catalyst such as platinum.

[0156] The silicone resin may be obtained from precursors which are advantageously soluble in the solvent or water of the emulsion, such as crosslinkable oils or resins, in particular chosen from: silanes, silicone oil resins containing at least one vinyl group (-CH=CH2), silicone resins or silicone-polyester resins (copolymers) containing at least one alkoxy group, such as methoxy or ethoxy, and / or silicone resins or silicone-polyester resins (copolymers) containing at least one alkoxy group, in particular ethoxy or hydroxyl, and mixtures thereof. These precursors have the ability to crosslink so as to obtain silicone resins characterized by their insolubility and their substantially solid form.

[0157] Advantageously, these precursors are polymers or oligomers, or in the form of silicone oils with variable branching, or in the form of silicone resins or silicone resin copolymers such as silicone-polyesters, silicone-alkyd resins, silicone-polyurethanes or silicone-epoxy resins with variable pre-crosslinking, or in the form of mixtures of silicone oils, silicone resins and silicone resin copolymers. The silicon atoms may be substituted by alkyl (especially methyl) or aryl (especially phenyl) groups or mixtures thereof. The oil or resin preferably contains one or more (2, 3 or more) hydroxyl or alkoxy (especially methoxy, ethoxy, butoxy) functional groups as substituents for the silicon atoms.

[0158] Advantageously, the one or more silicone resins obtained after crosslinking of their precursors, i.e. crosslinking, are chosen from methyl silicones and / or phenyl silicones and / or methyl-phenyl silicone resins, methyl silicone-polyester resins (copolymers), phenyl silicone-polyester resins (copolymers), methyl-phenyl silicone-polyester resins (copolymers), silicone resins-alkyd resins (copolymers), modified silicone resins and mixtures thereof.

[0159] Advantageously, the one or more silicone resins are selected from methyl silicone and / or phenyl silicone and / or methyl-phenyl silicone resin, methyl silicone-polyester resin (copolymer), phenyl silicone-polyester resin (copolymer), methyl-phenyl silicone-polyester resin (copolymer), silicone-alkyd resin (copolymer), modified silicone resin and mixtures thereof.

[0160] The silicone resin can be obtained from a precursor, which is particularly chosen from: silanes, silicone resins containing at least one vinyl group (-CH=CH2), silicone-polyester resins (copolymers) containing at least one methoxy group and / or silicone-polyester resins (copolymers) containing at least one ethoxy group, and mixtures thereof.

[0161] The silicone resin of the monolayer (3) forms a network which may consist of a combination of four single organosiloxane units denoted M, D, T and Q depending on the degree of substitution of silicon atoms by oxygen, as described in the table below, wherein R is an organic substituent as described below.

[0162]

[0163]

[0164] Organopolysiloxane materials or polymers are obtained by crosslinking precursors, which may be monomers or polymers, or in an intermediate manner, oligomers. Organopolysiloxane polymers may also be obtained from mixtures of these different types of precursors. The crosslinking density is higher when the network contains a greater number of T and Q units than D units. The distribution between M, D, T and Q units depends on the chemical structure of the precursors, in particular on the distribution of M, D, T, Q in the precursors.

[0165] The polymer precursor is an organopolysiloxane. These macromolecules are formed from the M, D, T and / or Q units described in the table, wherein R is independently an alkyl group, especially a methyl group, or an aryl group, especially a phenyl group, and different types of R can exist on the same macromolecule.

[0166] Organopolysiloxanes can be linear or slightly branched (mainly D groups), or branched or very branched (mainly T and Q groups). Straight-chain or slightly branched organopolysiloxanes are generally liquid, more or less viscous at ambient temperature, and are referred to as silicone oils. Branched or very branched (pre-crosslinked) organopolysiloxanes form networks on the scale of individual macromolecules and are referred to as silicone resins. The resins are substantially in solid form at ambient temperature, or in liquid form, provided that, in particular, they have a fairly low molecular weight, in the form of solutions in solvents or in the form of aqueous emulsions. They can be copolymerized with silicon-free organic polymers or oligomers, in particular selected from polyesters, acrylic resins, alkyd resins, polyurethanes and epoxy resins.

[0167] When the crosslinking is a hydrolysis-polycondensation: it is carried out using the hydroxyl or alkoxy reactive functional groups present on the organopolysiloxane, in particular the methoxy, ethoxy or butoxy groups.

[0168] When the crosslinking is polyaddition (or hydrosilylation): it is carried out by reaction between reactive vinyl functional groups (-CH=CH2) present on one of the organopolysiloxanes and reactive silyl-hydride functional groups (Si-H) present on the other organopolysiloxane mixed with the first organopolysiloxane.

[0169] All of these reactive functional groups are present in at least one number on each organopolysiloxane, and may be present in 2, 3 or more numbers as long as the molecular structure permits. Silicone oils containing at least one reactive functional group are referred to as "reactive oils". The reactive functional groups may be at the end (terminated) of the macromolecular chain, or distributed throughout the chain.

[0170] The silicone-polyester resin has, in particular, a silicone / polyester mass ratio of, for example, 90 / 10, 80 / 20, 70 / 30, 60 / 40, 50 / 50, 40 / 50, 30 / 70, 20 / 80, 10 / 90, advantageously between 80 / 20 and 50 / 50.

[0171] Linear PDMS silicone oils, pure or pre-emulsified in water, are mainly characterized by their molecular weight, which is a direct increasing function of the viscosity of the pure oil. They are then characterized by the presence of reactive functional groups or other aspects, such as hydroxyl groups on silicon atoms (silanols), their number and their position on the molecular chain. For example, reactive oils with viscosities between 50 and 20000 mPa.s, in particular between 300 and 5000 mPa.s, can be used, which have at least one reactive functional group, preferably at least 2, which functional groups can be located at the chain ends.

[0172] The polymer precursors that react by addition polymerization may include, for example, polymethylhydrogensiloxane, vinylmethylsiloxane, vinyl-terminated, especially linear polydimethylsiloxane (PDMS), vinyl-terminated diphenylsiloxane-dimethylsiloxane copolymers, hydride-terminated polydimethylsiloxane, hydride-terminated polyphenylmethylsiloxane, cyclic vinylmethylsiloxane, vinyl MQ resins, trimethylsilyl-terminated polymethylhydrogensiloxane, copolymers of trimethylsiloxane-terminated methylhydrogensiloxane and dimethylsiloxane, MQ resin hydrides, and the like, and combinations thereof.

[0173] The polymer precursors reacted by hydrolysis-polycondensation, whether they are silicone resins or silicone oils, may include, for example, poly(methylsilsesquioxane), poly(propylsilsesquioxane), poly(phenylsilsesquioxane), polydimethylsiloxane (PDMS), trimethylsilyl-terminated polydimethylsiloxane (PDMS), hydroxy-terminated polydimethylsiloxane (PDMS), silanol-terminated polyphenylsiloxane (PDMS), silanol-terminated copolymers of diphenylsiloxane-dimethylsiloxane, poly(2-acetoxyethylsilsesquioxane), organo-modified alkoxysilanes and their oligomers, and all similar macromolecules, as well as mixtures thereof.

[0174] The organopolysiloxane material or polymer can also be obtained by crosslinking a mixture of one or more monomer precursors and one or more polymer precursors as described above and one or more oligomeric precursors, which can be linear, branched or cyclic. These oligomeric precursors have a lower molecular weight than the polymer precursors. Polymers and / or oligomeric precursors containing more than 2, advantageously much more than 2, of the above-mentioned reactive functional groups can be added to the mixture as "co-binders" to promote the high crosslinking density of the organopolysiloxane polymer finally obtained.

[0175] The monomers, oligomers and / or polymer precursors, in particular silicone resins, copolymerized or not copolymerized with the organic polymers, act as polymeric binders to obtain solid organopolysiloxane polymers bonded to the thermoplastics of the layers.

[0176] If the silicone oil type organopolysiloxane precursor is added to the overall formulation of the layer in a small amount (typically 0.1 to 5% by dry weight), it can be considered an additive independent of the other components used to form the solid organopolysiloxane polymer.

[0177] Crosslinking may require a catalyst:

[0178] In the case of organopolysiloxanes crosslinked by hydrolysis-polycondensation, the formula may include metal catalysts, for example metal complexes based on platinum, tin, zinc, zirconium and cerium, in particular platinum-cyclovinylmethyl-siloxane complexes, tin ethylhexanoate complexes, zinc ethylhexanoate complexes, zirconium ethylhexanoate complexes, cerium ethylhexanoate complexes and dibutyltin laurate complexes.

[0179] In the case of crosslinking of the organopolysiloxane by hydroalkylation, it may be necessary to add a catalyst; this may be, for example, platinum or a suitable platinum-based catalyst, such as a Karstedt catalyst or an Ashbys catalyst.

[0180] Crosslinkers may be present, bearing for example Si-H bonds.

[0181] According to one embodiment, the proportion of the silicone resin in the layer ( 3 b ) is greater than or equal to 20% by weight, respectively, relative to the total weight of the layer ( 3 b ).

[0182] According to another embodiment, the proportion of silicone resin in the layer ( 3 b ) is greater than or equal to 40% by weight, respectively, relative to the total weight of the layer ( 3 b ).

[0183] According to a further embodiment, the proportion of the silicone resin in the layer (3b) is greater than or equal to 50% by weight, respectively, relative to the total weight of the layer (3b).

[0184] According to one embodiment, the proportion of silicone resin in the layer ( 3 c ) is greater than or equal to 20% by weight, respectively, relative to the total weight of the layer ( 3 c ).

[0185] According to another embodiment, the proportion of silicone resin in the layer ( 3 c ) is greater than or equal to 30% by weight, respectively, relative to the total weight of the layer ( 3 c ).

[0186] According to a further embodiment, the proportion of the silicone resin in the layer (3c) is greater than or equal to 40% by weight, respectively, relative to the total weight of the layer (3c).

[0187] According to a further embodiment, the proportion of the silicone resin in the layer (3c) is greater than or equal to 50% by weight, respectively, relative to the total weight of the layer (3c).

[0188] According to a further embodiment, the proportion of the silicone resin in the layer (3c) is greater than or equal to 60% by weight, respectively, relative to the total weight of the layer (3c).

[0189] According to one embodiment, the proportion of the silicone resin in one or more layers (3ab) is greater than or equal to 20% by weight relative to the total weight of the layer (3ab). According to another embodiment, the proportion of the silicone resin in one or more layers (3ab) is greater than or equal to 40% by weight relative to the total weight of the layer (3ab). According to yet another embodiment, the proportion of the silicone resin in one or more layers (3ab) is greater than or equal to 50% by weight relative to the total weight of the layer (3ab).

[0190] Thermoplastic polymers

[0191] Advantageously, the one or more thermoplastic polymers are selected from polyethersulfone (PES), polyphenylene ethersulfone (PPSU), polyamideimide (PAI), polyimide (PI), polyphenylene ether (PPO), polyarylether sulfide (PAS), polyetherimide (PEI), polybenzimidazole (PBI), liquid crystal polymer (LCP), polyphenylene sulfide (PPS), polyaryletherketone (PAEK) and mixtures thereof, wherein polyaryletherketone (PAEK) includes polyetherketone (PEK), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetheretherketoneketone (PEEKK), polyetherketoneetherketoneketone (PEKEKK).

[0192] Heterocyclic thermoplastic polymers

[0193] Heterocyclic thermoplastic polymers include, for example, polyetherimide (PEI), polyimide (PI), polyamideimide (PAI) and polybenzimidazole (PBI) according to the present invention, or mixtures thereof.

[0194] PAEK

[0195] Advantageously, the one or more polyaryletherketones (PAEK) are selected from the group consisting of polyetherketone (PEK), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetheretherketoneketone (PEEKK) and polyetherketoneetherketoneketone (PEKEKK), particularly preferably PEEK.

[0196] Advantageously, the nature of the thermoplastic polymer or polymers in layers (3b) and (3c) may be the same or different.

[0197] Advantageously, the layer (3b) comprises one or more thermoplastic polymers, preferably in a proportion by weight of less than 30%, preferably less than 20% of said layer.

[0198] Advantageously, the layer (3c) comprises one or more thermoplastic polymers, preferably in a proportion by weight of less than 50%, preferably less than 40% of said layer.

[0199] Advantageously, one or more layers (3ab) comprise one or more thermoplastic polymers, preferably in a proportion by weight of less than 50%, preferably less than 40% of said layer.

[0200] According to one embodiment, layer (3b) and layer (3c) comprise one or more thermoplastic polymers, the proportion of thermoplastic polymer in layer (3c) being preferably greater than the proportion of thermoplastic polymer in layer (3b).

[0201] According to another embodiment, layer (3b) and layer (3c) comprise one or more thermoplastic polymers, the proportion of thermoplastic polymer in layer (3b) being greater than the proportion of thermoplastic polymer in layer (3c).

[0202] filler

[0203] The fillers of the present invention provide mechanical reinforcement and may also provide hydrophobicity while improving the mechanical strength and thermal conductivity of the coating.

[0204] Fillers are not only there to provide color to the coating;

[0205] The presence of fillers with excellent thermal conductivity can compensate for the low thermal conductivity of PAEK polymer.

[0206] Advantageously, the filler or fillers are selected from ceramics (SiO2, etc.) and / or minerals and / or metals (Al2O3, TiO2, etc.) and / or silica and / or diamond particle fillers.

[0207] Preferably, the one or more fillers are selected from metal oxides, metal carbides, metal oxynitrides, metal nitrides and mixtures thereof.

[0208] Advantageously, the metal is a transition metal, for example at least one of the elements selected from B, Ni, Ti, Zr or Hf.

[0209] Still more preferably, the one or more fillers are selected from:

[0210] - Fillers for reinforcement: hard organic or inorganic fillers; hard inorganic fillers preferably have particles of silicon carbide or aluminum oxide or zirconium oxide, or graphite, or ceramics, or carbonates, or hydrated aluminum oxide, aluminum hydroxide or one or more metal oxides, graphene;

[0211] - other fillers for reinforcement, chosen from metal oxides: silica, mica, lamellar fillers, clays such as montmorillonite, sepiolite, gypsum, kaolinite and laponite, zinc dioxide, quartz and zirconium phosphate, alumina, zirconium oxide, zinc oxide, copper oxide and iron oxide;

[0212] - fillers chosen from reinforcing fibers: glass, carbon or aramid fibers;

[0213] - a conductive filler comprising a transition metal carbide and / or a transition metal nitride: characterized in that the transition metal is at least one element selected from B, Ni, Ti, Zr or Hf,

[0214] For example: cubic boron nitride, diamond particles, metal particles;

[0215] -Layered fillers, such as clay, graphene or graphite, can provide lubricity properties.

[0216] Preferred fillers for combination with organopolysiloxanes are:

[0217] - reinforcing fillers: silica or carbonates, filler content of at least 10-15% by weight and up to 60% by weight,

[0218] -alumina, hydrated alumina, aluminum hydroxide,

[0219] - silicon dioxide (precipitated or pyrogenic) with d50<0.1 μm and a specific surface area BET>30 m2 / g, preferably between 30 and 500 m2 / g,

[0220] -Mixtures of quartz and silicon dioxide, diatomaceous earth or quartz powder, titanium, mica, talc, kaolin, barium sulfate, slaked lime, zinc oxide, expanded vermiculite, unexpanded vermiculite, calcium carbonate, etc.

[0221] Still more preferably, the one or more fillers are selected from the group consisting of alumina, silicon carbide, tungsten carbide, boron nitride, quartz, and mixtures thereof.

[0222] Advantageously, the filler present in the bottom layer (3a) is a hard inorganic filler, preferably particles of silicon carbide or aluminum oxide or zirconium oxide or graphite, or carbon black, or ceramics, or one or more metal oxides.

[0223] Certain inorganic hard fillers such as silicon carbide, in addition to their mechanical reinforcement properties, have the advantage of being electrically conductive fillers, thus providing excellent thermal conductivity.

[0224] Adding this type of filler can improve cooking results with better heat diffusion from the metal base to the food in contact with the coating.

[0225] Advantageously, the filler has a median diameter d50 of from 0.1 to 50 μm, more advantageously from 5 to 15 μm.

[0226] Advantageously, the proportion of filler in the layer is between 0.5 and 30% by dry weight, preferably between 5 and 20% by dry weight, relative to the total weight of said layer after curing.

[0227] Advantageously, the proportion of filler in layer (3a) is greater than 20% by weight, preferably greater than 30% by weight, relative to the total weight of said layer.

[0228] Advantageously, the proportion of filler in layer ( 3 c ) is less than 10% by weight relative to the total weight of said layer.

[0229] Advantageously, the proportions of fillers in layers (3a), (3ab), (3b) and (3c) may be the same or different.

[0230] Advantageously, the nature of the fillers in layers (3a), (3ab), (3b) and (3c) may be the same or different.

[0231] additive

[0232] Advantageously, the additive is selected from the group consisting of a defoamer, a dispersant, a wetting agent, a thickener, a pH adjuster, and a reactive silicone oil.

[0233] The one or more defoamers are preferably selected from mineral oils, glycols, hydrocarbons, glycerides, ethylene oxide and emulsified fatty acids.

[0234] The one or more surfactants are preferably selected from glycol ethers, ethoxylated alcohols other than alkylphenol ethoxylates (APE), gemini surfactants.

[0235] The one or more dispersants are preferably selected from the group consisting of anionic dispersants, such as fatty acid derivatives.

[0236] The thickener is preferably selected from the group consisting of acrylic or polyurethane based copolymers, cellulose and fumed silica.

[0237] The pH adjuster is preferably selected from the group consisting of Bronsted bases: ammonia, amines (triethylamine, triethanolamine, ...), (sodium, potassium, etc.), hydroxides, carbonates.

[0238] Advantageously, the proportion of additives in layer ( 3 a ) is less than 1% by weight relative to the total weight of said layer.

[0239] Advantageously, the proportion of additives in layer ( 3 c ) is less than 20% by weight relative to the total weight of said layer.

[0240] Advantageously, the proportion of additives in one or more layers ( 3ab ) is less than 20% by weight relative to the total weight of said layer(s).

[0241] Colorants

[0242] Advantageously, the colorant or colorants are chosen from thermochromic pigments, heat-stable pigments, flakes, preferably holographic flakes, and mixtures thereof.

[0243] Advantageously, the proportion of colorant in layer (3b) and layer (3c) is between 0.5 and 50% by dry weight relative to the total weight of said layer after curing.

[0244] Advantageously, the proportion of colorant in layer (3b) ranges from 10% to 40% by weight relative to the total weight of said layer.

[0245] Advantageously, the proportion of colorant in layer (3c), when present, is less than 10% by weight relative to the total weight of said layer.

[0246] Advantageously, the proportions of colorants in layers (3b) and (3c) may be the same or different.

[0247] Advantageously, the nature of the colorants in layers (3b) and (3c) may be the same or different.

[0248] Thermochromic Pigments

[0249] Preferably, the one or more thermochromic pigments are selected from Bi2O3, Fe2O3, V2O5, WO3, CeO2, In2O3, Y 1.84 Ca 0.16 Ti 1.84 V 0.16 O 1.84 ,AgI or (Bi 1-x A x )(V 1-y M y )O4, where

[0250] -x is equal to 0 or x is between 0.001 and 0.999,

[0251] -y is equal to 0 or y is between 0.001 and 0.999,

[0252] - A and M are selected from nitrogen, phosphorus, alkali metals, alkaline earth metals, transition metals, poor metals, semimetals or lanthanides,

[0253] -A and M are different from each other.

[0254] It is known that A and M are different from each other, at this time:

[0255] - A is an alkali metal, which can be selected from Li, Na, K, Rb, Cs,

[0256] - M is an alkali metal, which can be selected from Li, Na, K, Rb, Cs,

[0257] - A is an alkaline earth metal, which can be selected from Be, Mg, Ca, Sr, Ba,

[0258] - M is an alkaline earth metal, which can be selected from Be, Mg, Ca, Sr, Ba,

[0259] - A is a transition metal, which can be selected from Sc, Ti, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Ta, W, Ir,

[0260] - M is a transition metal, which can be selected from Sc, Ti, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Ta, W, Ir,

[0261] -A is a poor metal, which can be selected from Al, Zn, Ga, In, Sn,

[0262] -M is a poor metal, which can be selected from Al, Zn, Ga, In, Sn,

[0263] - A is a semimetal, which can be selected from B, Si, Ge, Sb,

[0264] -M is a semimetal, which can be selected from B, Si, Ge, Sb,

[0265] - A is a lanthanide element, which can be selected from La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu,

[0266] -M is a lanthanide element, which can be selected from La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu.

[0267] Preferably, A and M are different from each other and are B and / or Mg.

[0268] Preferably, the pigment (Bi 1-x A x )(V 1-y M y )O4 has the crystalline form of monoclinic scheelite at ambient temperature.

[0269] Preferably, x and y are 0, that is, the pigment (Bi 1-x A x )(V 1-y My )O4 is bismuth vanadate (BiVO4). Advantageously, BiVO4 is used, which has a monoclinic scheelite structure at ambient temperature.

[0270] Bismuth vanadate is a yellow inorganic compound with the formula BiVO4, which is widely used due to its coloring properties and non-toxicity. It is entered into the Colour Index International as QIPigment Yellow 184 and it is specifically developed by Heubach BASF , FERRO (Lysopac) or Bruchaler Farbenfabrik Sale.

[0271] Heat stable pigments

[0272] Preferably, the one or more heat stable pigments are selected from the group consisting of:

[0273] -Titanium Rutile Yellow Pigment,

[0274] - yellow pigments derived from bismuth, for example selected from stable bismuth vanadates (Py 184 )

[0275] - red pigments, for example selected from perylene red (e.g. PR 149 , PR 178 and PR 224 ), iron oxide,

[0276] -Bismuth oxyhalide orange pigment (PO 85 ),

[0277] -Bismuth vanadate orange pigment (PO 86 )

[0278] -Tin-Titanium-Zinc Orange Pigment (PO 82 )

[0279] -Cerium sulfide orange pigment (PO 75 PO 78 )

[0280] -Chrome antimony titanium rutile orange pigment (PBr 24 )

[0281] -Zinc Tin Gold Rutile Orange Pigment (Py 216 )

[0282] -Zinc tin sulfide niobium oxide orange pigment (Py 227 )

[0283] -Niobium tin double oxide orange pigment

[0284] -Co3(PO4)2

[0285] -LiCoPO4

[0286] -CoAl2O4

[0287] -Cr2O3

[0288] -TiO2

[0289] -Black Pigment PBk28 (Copper Chromite Black Spinel)

[0290] - and mixtures thereof.

[0291] decorate

[0292] According to one embodiment, the one or more layers (3b) are continuous and cover the entire layer (3a) (see Figure 1 ).

[0293] According to another embodiment, one or more layers (3b) do not cover the entire layer (3a) and form at least one decoration (see Figure 2 ).

[0294] Advantageously, one or more layers (3b) form a plurality of decorations, one layer (i) comprising one or more thermochromic pigments and another layer (j) comprising at least one reference temperature pigment composition (cf. Figure 3 ).

[0295] According to one embodiment, each of the two decorations (i) and (j) is in the form of non-overlapping adjacent patterns. For example, each decoration is represented by different geometric patterns that are evenly distributed over the entire surface and alternate with respect to each other (see Figure 4 A).

[0296] According to another embodiment, the two decorations (i) and (j) partially overlap. For example, each decoration is represented by a different geometric pattern evenly distributed over the entire surface and partially overlapping (see Figure 4 B).

[0297] Preferably, the two decorations (i) and (j) overlap, either because one of the two decorations is a continuous layer and the other decoration covers the continuous layer in the form of a pattern, or because the two decorations (i) and (j) are in the form of overlapping patterns (see Figure 4 C).

[0298] Thin slice

[0299] The flakes useful in the present invention may be independently selected from coated or uncoated mica flakes, coated or uncoated silica flakes, coated or uncoated aluminum flakes, and coated or uncoated iron oxide flakes. Mica or silica flakes coated with titanium dioxide. The flakes useful in the present invention may be treated to produce a specific color effect.

[0300] Advantageously, the one or more flakes are chosen from the group consisting of particles of mica, aluminum, titanium dioxide coated mica or mixtures thereof.

[0301] Holographic Sheets

[0302] Advantageously, the one or more flakes are holographic flakes, ie a mixture of magnetizable particles and non-magnetizable particles.

[0303] The magnetizable particles may advantageously be particles comprising at least one ferromagnetic metal. These magnetizable particles may be homogeneous, i.e. formed from the same material, or composite, i.e. these magnetizable particles have a core-shell structure, wherein the ferromagnetic metal is located in the core and / or shell of the particles. Examples of composite magnetizable particles include in particular mica flakes coated with iron oxide Fe2O3 or stainless steel fibers coated with a sol-gel material as a corrosion protection during the coating step, or flakes made of plastic material and coated with iron oxide Fe2O3, or flakes whose core is made of a ferromagnetic metal and whose shell is formed of a plastic material or a sol-gel material.

[0304] According to an embodiment, some of the magnetizable particles are oriented to form a three-dimensional decoration.

[0305] Advantageously, the mixture of magnetizable particles and non-magnetizable particles represents between 1% and 5% by weight, preferably between 2% and 3% by weight, of the weight of the layer.

[0306] Advantageously, the percentage of non-magnetizable particles in the mixture of magnetizable and non-magnetizable particles is between 15% and 40% by weight relative to the total weight of the mixture.

[0307] Advantageously, the magnetizable particles have a size D50 of less than or equal to 23 μm.

[0308] In the context of the present invention, the term "D50" shall mean the largest dimension exhibited by 50% by number of the particles.

[0309] Advantageously, the non-magnetizable particles have a size D90 which is between 20% and 250% of the size D90 of the magnetizable particles.

[0310] In the context of the present invention, the term "D90" shall mean the largest dimension exhibited by 90% by number of the particles.

[0311] Advantageously, the magnetizable particles and / or the non-magnetizable particles are colored on the surface.

[0312] Advantageously, the non-magnetizable particles are in the form of mica, aluminium or mica coated with titanium dioxide.

[0313] Advantageously, the magnetizable particles are formed from iron, iron oxide, aluminum coated with iron or mica coated with iron, the iron being in the form of ferrite.

[0314] Preferred architecture

[0315] Advantageously, the invention relates to a coated cooking element (1) for a cooking appliance or electric cooking utensil, comprising a metal substrate (2) coated on at least one face (2a) with at least the following layers, in order starting from the metal substrate (2):

[0316] (3a) a porous hard substrate, which consists of one or more polyether aryl ketones (PEAK) and mixtures thereof, optionally fillers, optionally less than 3 wt. % additives relative to the weight of the hard substrate, and optionally less than 3 wt. % colorants relative to the weight of the hard substrate,

[0317] (3b) Optionally, one or more decorations, including one or more colorants

[0318] (3c) a finishing layer, the finishing layer consisting of one or more silicone resins and optionally:

[0319] - one or more thermoplastic polymers, and / or

[0320] - one or more fillers, and / or

[0321] - one or more additives.

[0322] Typically, the average thickness of the hard bottom layer (3a) is between 20 μm and 50 μm. The average is the average of at least 10 measurements, preferably 15 measurements, of the thickness at, for example, 10 or 15 random locations.

[0323] Preferably, the colorant of the intermediate layer(s) (3b) comprises pigments and / or flakes, advantageously holographic flakes.

[0324] According to an alternative, the intermediate layer or layers (3b) consist of:

[0325] one or more colorants, in particular pigments and / or flakes, advantageously holographic flakes,

[0326] one or more thermoplastic polymers, advantageously chosen from polyamideimide (PAI), polyimide (PI), polyetherimide (PEI), polybenzimidazole (PBI), polyethersulfone (PES), polyphenylene ethersulfone (PPSU), polyaryletherketone (PAEK) and mixtures thereof,

[0327] 0 to 10% filler,

[0328] 0 to 20% additives,

[0329] ●Optionally one or more silicone resins.

[0330] According to another alternative, the intermediate layer or layers (3b) consist of:

[0331] one or more colorants, in particular pigments and / or flakes, advantageously holographic flakes,

[0332] 0 to 10% filler,

[0333] 0 to 20% additives,

[0334] ● one or more silicone resins, and

[0335] - optionally, one or more thermoplastic polymers, advantageously selected from polyamideimide (PAI), polyimide (PI), polyetherimide (PEI), polybenzimidazole (PBI), polyethersulfone (PES), polyphenylene ethersulfone (PPSU), polyaryletherketone (PAEK) and mixtures thereof,

[0336] According to one particular variant, the intermediate layer or layers ( 3 b ) do not comprise silicone resin.

[0337] According to another particular alternative, the intermediate layer or layers (3b) consist of:

[0338] one or more colorants, in particular pigments and / or flakes, advantageously holographic flakes,

[0339] one or more thermoplastic polymers, advantageously chosen from polyamideimide (PAI), polyimide (PI), polyetherimide (PEI), polybenzimidazole (PBI), polyethersulfone (PES), polyphenylene ethersulfone (PPSU), polyaryletherketone (PAEK) and mixtures thereof,

[0340] 0 to 10% filler,

[0341] 0 to 20% additives,

[0342] • One or more silicone resins.

[0343] According to one embodiment, the coating comprises two intermediate layers (3b), at least one of which is a decorative layer. Advantageously, one or more layers (3b) form a plurality of decorations, one layer (i) comprising one or more thermochromic pigments and another layer (j) comprising at least one reference temperature pigment composition.

[0344] Advantageously, the thickness of the layer ( 3 b ) is between 1 μm and 100 μm, preferably between 2 μm and 30 μm, particularly preferably between 3 μm and 10 μm.

[0345] Preferably, the one or more intermediate layers (3b) only cover a portion of the base layer (3a).

[0346] Alternatively, according to another embodiment, the coating is free of an intermediate layer (3b).

[0347] According to one embodiment, the finishing layer (3c) consists of one or more silicone resins and optionally one or more thermoplastic polymers.

[0348] According to another embodiment, the finishing layer (3c) consists of one or more silicone resins and one or more thermoplastic polymers.

[0349] Advantageously, the thickness of the layer ( 3 c ) is between 0.05 μm and 100 μm, preferably between 0.08 μm and 20 μm, particularly preferably between 0.1 μm and 10 μm.

[0350] In a specific embodiment, the average thickness of the hard bottom layer (3a) is between 20 and 50 μm, the thickness of the layer (3b) is between 3 and 10 μm, and the thickness of the layer (3c) is between 0.1 μm and 10 μm. The average thickness of the hard bottom layer (3a) is the average of at least 10 measurements, preferably 15 measurements, of the thickness at, for example, 10 or 15 random positions.

[0351] method

[0352] The method also relates to a method for manufacturing a coated cooking element (1) according to the invention, comprising the following successive steps:

[0353] a) providing a metal support (2) comprising two opposing surfaces;

[0354] b) optionally, a step of treating the face (2a) of the support (2) to obtain a treated face (2a) that promotes the adhesion of the hard bottom layer (3a) on the support (2);

[0355] c) a step of producing an adherent hard base layer (3a) on said inner face (2a) by thermally spraying onto said inner face (2a) a powder or dispersion of one or more polyether aryl ketones (PEAK) and mixtures thereof, optionally fillers, optionally less than 3% by weight of additives relative to the weight of said hard base layer (3a) and optionally less than 3% by weight of colorants;

[0356] d) optionally drying and / or curing;

[0357] e) optionally applying the one or more layers (3ab) and / or one or more intermediate layers (3b);

[0358] f) applying the finishing layer (3c);

[0359] g) drying and / or curing.

[0360] Advantageously, the steps of the method according to the invention make it possible to coat the metallic support ( 2 ) with a coating ( 3 ) formed by the layers ( 3 a ), optionally ( 3 ab ), ( 3 b ) and ( 3 c ).

[0361] Typically, layers (3ab), (3b) and (3c) are wet when applied. In the context of the present invention, "wetting layer" shall mean that the layer contains all or part of its solvent.

[0362] Preferably, all or part of the solvent of the wetting layer is removed naturally or by physical treatment, such as thermal drying, drying by a stream of air or by vacuum treatment.

[0363] Advantageously, the coating composition according to the invention may further comprise at least one solvent. Advantageously, the solvent may be a protic solvent. Advantageously, the solvent may be non-toxic.

[0364] The solvent that can be used in the coating composition of the present invention may advantageously comprise at least one alcohol, and may preferably be selected from isopropanol, methanol, ethanol, and mixtures thereof.

[0365] The application of the coating is carried out in multiple layers. In this case, the deposition of at least one layer of the coating (3) according to the invention on at least one of the two opposite faces of the support is repeated several times. Preferably, a drying step is carried out between the application of each layer, and then curing of the coated support is carried out after the application of the last layer. The application of the coating (3) on the support (2) by the method according to the invention makes it possible to obtain a layer of thermally stable coating.

[0366] The coating formulation to be applied is usually in aqueous form, with the polymer of the polymer phase being in suspension form. Other non-aqueous solvents are also suitable.

[0367] Advantageously, the method for manufacturing a coated cooking element (1) according to the invention comprises one or more drying steps between 80° C. and 150° C. after application of each of the layers. Drying can be carried out by convection or infrared.

[0368] The application of the coating according to the invention by the method according to the invention can be carried out on the shaped support or even on locally flat areas of the shaped support. A thermally stable coating is obtained.

[0369] Advantageously, the method for manufacturing a coated cooking element (1) according to the invention comprises, before step c., a step of shaping the metal support (2). Shaping is also known as stamping.

[0370] When the shaping step precedes step ii. of applying the coating, the coating is preferably carried out by spraying.

[0371] When this shaping step follows step vii. of applying the coating, the coating is preferably carried out by screen printing or by roller printing.

[0372] The method according to the invention comprises a step g. of curing / drying the element obtained in step f. of the method. In the context of the present invention, "curing the coated substrate" means a thermal treatment which densifies the coating or coatings applied on the substrate and crosslinks the organopolysiloxane (silicone resin) precursor.

[0373] Curing is performed in step g. Typically, the curing temperature in step g. is between 230°C and 420°C.

[0374] Advantageously, the method for manufacturing a coated cookware (1) according to the invention comprises a single final curing step g. of all the applied layers. This single curing step is carried out simultaneously on all the applied layers.

[0375] As its name indicates, thermal spraying consists of spraying a powder or dispersion onto a surface.

[0376] Preferably, in step a), the metal support (2) is in the form of a disc.

[0377] Advantageously, the method according to the invention does not comprise a further curing step than that of step g).

[0378] Preferably, thermal spraying is spraying by means of spraying ("flame spraying") or cold gas dynamic spraying ("cold spraying").

[0379] The spraying of the powder portion associated with at least partial melting of the non-fluorinated polymer material during flame spraying explains the discontinuity of the hard bottom layer (3a).

[0380] Preferably, the material to be sprayed is a powder material having a particle size distribution D50 of 5 to 60 μm, preferably 10 to 35 μm.

[0381] Preferably, in flame spraying, a step of preheating the support (2) at low temperature is carried out before step c) of producing the hard bottom layer (3a). The preheating is carried out at a maximum temperature of 100°C.

[0382] Preferably, in cold spraying, a step of preheating the support (2) to a temperature between 150°C and 300°C is carried out before step c) of producing the hard bottom layer (3a).

[0383] Preferably, curing step (g) is carried out in an oven at a temperature of from 230°C to 420°C.

[0384] The application step (f) and step (e) of applying one or more layers (3ab) can be carried out by electrostatic powder coating, solvent phase or aqueous phase spraying, screen printing, roller printing or digital printing.

[0385] The step (e) of applying one or more intermediate layers (3b) can be performed by pad printing, screen printing, flexographic printing, inkjet.

[0386] Utensils

[0387] The invention also relates to a cooking utensil (100) comprising a coated cooking element (1).

[0388] According to one embodiment, the cooking appliance (100) comprises a heating surface (6) for placement in contact with an external heating source, the heating surface (6) being opposite to a cooking surface (5) for placement in contact with food during cooking.

[0389] Advantageously, the cooking utensil (100) according to the invention is selected from the group consisting of a frying pan, a frying pan, a pot or a pot for fondue or raclette, a stew pot, a wok, a frying pan, a pancake maker, a grill, a frying pan, a casserole, a container for a cooker or a bread maker, and a cooking mold.

[0390] The invention also relates to an electric cooking appliance (200) comprising a coated cooking element (1) according to the invention and a heating source (210) designed to heat the coated cooking element (1).

[0391] Advantageously, the electric cooking appliance (200) is selected from the group consisting of an electric pancake maker, an electric raclette appliance, an electric fondue appliance, an electric grill, an electric pancake grill, an electric rice cooker, a bread maker or an electric pressure cooking appliance waffle maker, an electric rice cooker and a jam maker.

[0392] The cooking utensil according to the invention may in particular be a cooking utensil in which one of the two opposite faces of the base is an inner, optionally concave face intended to be arranged on the side of food that may be introduced into or on the utensil, and the other face of the base is an outer, optionally convex face intended to be arranged facing a heat source.

[0393] By way of non-limiting example, cooking utensils according to the invention include in particular cooking utensils such as pots and pans, woks and kettles, stew pots and casseroles, pancake makers, baking and fig dishes, grilling trays and grills and preparation bowls.

[0394] Examples and Results

[0395] The objectives, aspects and advantages of the invention will be better understood on reading the following description of particular embodiments of the invention presented by way of non-limiting example.

[0396] Of course, the present invention is in no way limited to the described and illustrated embodiments, which are provided only as examples. Modifications may still be made without exceeding the scope of protection of the present invention, especially from the perspective of the composition of the various elements or by replacement of technical equivalents.

[0397] raw material:

[0398] The raw materials of layer (3a) are described in detail below.

[0399] The raw materials of the middle layer (3b and 3b') and the finishing layer (3c) are as follows:

[0400] -Silicone resin:

[0401] o RS1: Ethoxy-functional silicone-polyester resin (80% silicone / 20% polyester) in solvent phase, viscosity of about 2000 at 25°C

[0402] mPas, solid content = 75%

[0403] o RS2: Ethoxy-functional silicone-polyester resin (50% silicone / 50% polyester) in solvent phase, viscosity of about 2000 at 25°C

[0404] mPas, solid content = 75%

[0405] o RS3: Ethoxy-functional silicone-polyester resin (30% silicone / 70% polyester) in solvent phase, viscosity of about 2000 at 25°C

[0406] mPas, solid content = 75%

[0407] o RS4: Methylphenyl functionalized silicone-polyester resin in solvent phase, viscosity about 2000 mPas at 25°C, solids content = 75%

[0409] o RS5: a methoxy-functional silicone-polyester resin (50% silicone / 50% polyester) in solvent phase with a viscosity of approximately 2000 at 25°C

[0410] mPas, solid content = 75%

[0411] o RS6: Ethoxy-functional methyl organopolysiloxane resin in aqueous emulsion, viscosity about 1500 mPas at 25°C, solids content = 52%

[0412] -Heterocyclic polymer resins:

[0413] o Polyamide-imide resin (PAI), 29% dry extract in N-butylpyrrolidone (NBP), Torlon from SOLVAY

[0414] -Other aromatic polymer resins:

[0415] o Powdered polyetheretherketone (PEEK), Vicote from Victrox

[0416] 703, powder polymer with d50 of 25 μm,

[0417] o Powdered polyetheretherketone (PEEK), Vicote from Victrox

[0418] 704, powder polymer with d50 of 10 μm,

[0419] o Powdered PEKK resin, KEPSTAN 7002 from Arkema

[0420] PT, d50 is 20 μm,

[0421] o Powder PEKK resin, KEPSTAN 6002PT from Arkema, d50 of 50 μm,

[0422] o Powdered polyethersulfone (PES) resin, micronized grade from SOLVAY, polymer powder with d50 of 40 μm.

[0423] -Alcohol solvent

[0424] oDipropylene glycol butyl ether (DPNB),

[0425] o 2-Methoxy-1-methylethyl acetate (MPA),

[0426] oButylene glycol acetate (BGA),

[0427] oButyl acetate,

[0428] -Surfactants and defoamers

[0429] o Mineral oil: Tego Foamex K7 from Evonik

[0430] o Fatty alcohol polyglycol ethers: Genapol X080, from Clariant or TergitolTMN-100X,

[0431] -Reinforcing fillers:

[0432] o Fumed silica: Levasil CC301,

[0433] o Fumed silica post-treated with dimethyldichlorosilane: Aerosil R972

[0434] -pigment:

[0435] o Mica: IRIODIN 100 or IRIODIN 300 and / or Magnapearl 5000,

[0436] o Cr / Fe oxide: SiCopal Black K0098FK,

[0437] o Carbon black: Derussol F25 or Cabot Monarch 4750,

[0438] oPaliogen red (PR178)

[0439] oIron Oxide III: H856 Brick

[0440] -Acrylic resin:

[0441] o Rohagit SD 15: 30% acrylic polymer solution in water

[0442] -Silicone oil:

[0443] o Polyether modified polysiloxane: TEGO GLIDE 100,

[0444] oDimethicone oil: CT 601M

[0445] -Other additives:

[0446] o AMP 90: Solution of 2-amino-2-methyl-1-propanol: 90% polymer in water, buffer,

[0447] o Metlot368: fatty acid esters,

[0448] o Dolfynox 1030: Propoxylated polyglycol ether, wetting agent,

[0449] o Edaplan LA 451: solution of anionic ester in ethanol / water, wetting agent

[0450] o Tego Glide 407: Methylphenyl polysiloxane, flow agent.

[0451] Principle of Operation of Jar Mill (Mechanical Grinder):

[0452] Ball milling involves loading the sample to be ground and the so-called grinding balls into a jar and rotating the jar around its axis at a certain speed. The rotation of the jar is usually achieved using a roller mill. The sample can be ground in dry form or dispersed in a suitable solvent (for example in water or alcohol). The dispersion can also contain certain additives (for example dispersants or defoamers).

[0453] The median diameter of the grinding balls must be adapted to the size of the particles to be ground. The finer the particles, the smaller the diameter of the balls used. The total volume of the balls including the spaces between the balls will account for approximately 50-60% of the internal volume of the jar. The balls of different sizes are advantageously distributed according to the following weight proportions relative to the total weight of the balls: small balls 25%, medium balls 50%, large balls 25%. The minimum size of the balls is between 2 and 10 mm. Stabilized aluminum oxide and zirconium oxide are generally used as materials for the balls.

[0454] test

[0455] Mechanical shock (ball impact) test:

[0456] The impact resistance of non-stick coatings was evaluated by the Erichsen test according to standard ISO 6272.

[0457] This involves an impact test by dropping a 2 kg ball from a height of 50 cm. Aluminum or stainless steel plates are used for the tests, if appropriate one of which is coated with the two-layer coating according to the invention. The plates are identical to one another (in terms of thickness and the nature of the alloy) in order to have a constant deformation for all tests.

[0458] The test involves impacting the coating deposited directly on the coated surface of a plate (internal punch test) and impacting the surface opposite the coated surface of another plate (external punch test).

[0459] After impacting, the coated side of the coating was visually inspected.

[0460] The impact resistance of the coatings was evaluated according to a visual scale, establishing a visual score on the one hand after direct impact on the coating (internal impact test) and on the other hand on the side opposite to the side on which the coating was applied (external impact test).

[0461] - The attribute is scored as 0 if the following is observed:

[0462] For internal punch tests:

[0463] At the point of impact, the coating over the entire deformed surface of the inner face completely delaminated, which was indicated by the appearance of a "white" area at the point of impact (corresponding to the portion of the metal surface without coating) in the form of a disk of the order of 25 mm in diameter.

[0464] For external punch tests:

[0465] Moreover, over a large area of ​​the deformed inner surface the coating completely delaminated, which was evident by the appearance of a "white" area (corresponding to a portion of the metal surface without coating) at the impact point, which area was in the form of a disk having a diameter of at least 10 mm.

[0466] - A score of 1 is assigned if the following is observed:

[0467] For internal punch tests:

[0468] On impact, the coating delaminated almost completely over a large area of ​​the deformed inner face, this delamination being indicated by the appearance of an almost "white" area (corresponding to a portion of the metal surface without coating) on ​​impact, in the form of a disk of the order of 20 mm in diameter.

[0469] For external punch tests:

[0470] In the middle region of the deformed inner face, the coating delaminated almost completely, which was evident by the appearance of a coating-free "white" area at the impact point in the form of a disk having a diameter of about 10 mm.

[0471] - A score of 2 is assigned if the following is observed:

[0472] For internal punch tests:

[0473] Upon impact, the coating delaminated almost completely over the middle region of the coated inner face, which was evident by the appearance of a coating-free "white" area at the impact point in the form of a disk having a diameter of about 10 mm.

[0474] For external punch tests:

[0475] At the impact point, a white area in the form of a disk with a diameter less than 10 mm, in which there are large fragments, extends to the metal surface of the carrier with a relatively high fragment density.

[0476] - A score of 3 is assigned if the following is observed:

[0477] For internal punch tests:

[0478] At the impact point, the central area where large fragments are located allows the metal to be revealed.

[0479] For external punch tests:

[0480] Upon impact, a white surface in the form of a disk less than 10 mm in diameter with fine fragments extending to the metal with a moderately high density.

[0481] - A score of 4 is assigned if the following is observed:

[0482] For internal punch tests:

[0483] At the point of impact, an area in the form of a small-diameter disk with fine fragments extends to the metal with a rather low density.

[0484] For the external punch test, some of the indentations reach down to the metal, which is located at the point of impact.

[0485] Finally, the attribution is a score of 5 if the following is observed:

[0486] For internal punch tests:

[0487] At the point of impact, a slight halo was seen, slightly lighter than the coating.

[0488] For external punch tests:

[0489] There was no change in coating appearance.

[0490] The higher the score obtained, the better the impact resistance of the coating.

[0491] SEM / EDXS characterization:

[0492] SEM is a versatile and multifunctional device that can obtain surface structure and morphology images of materials with a resolution of a few nm and a large depth of field; it also provides mass (BSE) chemical information and quantitative chemical information (EDXS, with a lateral resolution of about 1 μm).

[0493] EDXS is a technique in which the X-rays produced by the interaction between an electron beam and a sample are analyzed to give the elemental composition of the sample. The EDXS spectrum includes peaks corresponding to the characteristic radiation of specific elements. Quantitative chemical characterization of the sample is deduced from the EDXS spectrum.

[0494] The SEM-EDXS analysis technique can combine topographic surface analysis using scanning electron microscopy (SEM) with chemical analysis using energy dispersive X-ray spectroscopy (EDXS).

[0495] The principle of SEM is based on the detection of secondary electrons. An electron beam (called primary electrons) comes into contact with the surface of a sample. When colliding with atoms present at the surface, the primary electrons can release energy to the electrons in the outer shells of these atoms. These electrons are then emitted and are called secondary electrons. Analysis of these electrons from the surface layer provides information about the morphology. When primary electrons collide with atoms, these atoms can enter an excited state. When returning to a stable state, they emit X-rays with wavelengths that are characteristic of the properties of the atoms. Therefore, analysis of these X-rays provides information about the chemical properties of the sample.

[0496] Physicochemical analysis of the surface by SEM-EDXS analysis also revealed the macroporosity of the PEEK or PEEK / SiC substrate.

[0497] Due to the accumulation of partially melted PEEK particles, a layer with very high porosity is obtained.

[0498] The spray-spread silicone coating can penetrate into the macropores of the underlying layer; after crosslinking of the silicone resin, this produces a composite material without the need for post-processing (heat pressing, etc.).

[0499] Silicone, optionally in the presence of silicon carbide fillers, becomes interpenetrated by the macromolecular chains of PEEK, which produces a dense network with excellent mechanical properties ( Figure 5 ).

[0500] The porosity evaluation test was conducted by X-ray microtomography.

[0501] X-ray micro-microtomography is a powerful non-destructive testing technique that can produce a 3D magnified image of a sample. Its operation is based on the same physical principles as medical scanners and can achieve better spatial resolution of less than a micron. The technique involves acquiring a large number of radiographic projections of the sample from multiple angles to digitally reconstruct a 3D map of the phases that make up the sample.

[0502] X-ray radiography involves passing an X-ray beam through a sample and measuring the spatial distribution of the beam intensity leaving the sample on a detector.

[0503] Various X-ray sources can be used for X-ray microtomography, in particular X-ray tubes and synchrotrons. These two types of sources have different properties, which affect microtomography acquisition.

[0504] For our analysis, the source used is a synchrotron, which, unlike an X-ray tube, emits a parallel X-ray beam. The enlargement of the radiographic projection is performed by a detector. This includes an optical system that can be adjusted to select the desired size of the pixel. Therefore, it is not necessary to bring the sample and the source closer together in order to increase the acquisition resolution, which makes it possible to overcome the limitations on the size of the object and to use pixel sizes of less than 1 μm.

[0505] The X-rays used in radiography have sufficient energy to pass through most materials; they are only slightly absorbed by lighter elements and can pass through large thicknesses of matter. As the X-ray beam passes through a sample, it is affected by various physical mechanisms that manifest themselves by a reduction in its intensity until it exits the sample. This attenuation is proportional to the thickness of the phase passed through and to the attenuation coefficient. Therefore, each unit sensor of the detector measures an intensity that depends on the path through the material that the beam has passed. These local intensity measurements are then digitized and converted to form a grayscale image, called a radiograph or radiographic projection.

[0506] Radiographic systems may also generate magnifications of the projected images either by the geometry of the beam emitted by the X-ray source or via the detection system.

[0507] Low-density areas correspond to low gray levels (almost black), while high-density areas correspond to high gray levels (almost white). The contrast of these gray levels makes it possible to distinguish phases of different densities.

[0508] The grayscale distribution in microtomography data can be visualized on a histogram. The grayscale histogram provides information, in particular, about the volume fractions of the individual phases of the sample.

[0509] Scratch resistance test (scratch test):

[0510] Using a Rockwell diamond tip with a radius of 200 μm, a load is gradually applied in the coating, increasing the applied force from 0 to 20 Newtons. The traces of the scratches are then observed by optical microscopy. The recorded delamination value of the coating corresponds to the force at which a clear crack up to the metal is observed in the film. For all the tests, the parameters of the speed of the load increase and the speed of movement of the tip remain constant.

[0511] For each sample, 5 scratches were performed and the average of the 5 delamination values ​​at the metal was recorded.

[0512] Example 1: Porous PEEK base layer + silicone on aluminum

[0513] Process:

[0514] -raw material

[0515] PEEK (polyetheretherketone) is sold under the trade name VICTREX VICOTE 703 is manufactured and sold, with a diameter of D5025 μm, a glass transition temperature of 143°C and a melting temperature of 343°C.

[0516] - Equipment: flame blowtorch, Eutectic-Castodyn Castodyn DS8000, reference flame nozzle Eutectic-Castodyn module SSMA40.

[0517] - The moving speed of the blowtorch is 150mm / s to 200mm / s

[0518] -Dual powder feeder, Sulzer Metco, and powder mix flow: variable from 2 to 7 g / min

[0519] -Thickness of the bottom layer: between 10 and 50 μm

[0520] - Propellant gas: Compressed air

[0521] - Fuel gas: 10 to 16 l / min of acetylene, 0.5 to 1 bar of acetylene

[0522] -Fuel gas: oxygen varied from 10 to 20.0 l / min, oxygen pressure varied from 3 to 5 bar

[0523] - Temperature of the carrier during application of the hard base: greater than or equal to ambient temperature (of the order of 20 to 250° C.)

[0524] - Application distance from the blowtorch to the workpiece, between 10 and 20 cm

[0525] - Workpiece rotation speed, between 400 and 800 rpm

[0526] The thermal spraying method by flame spraying or flame thermal spraying is a method for manufacturing cooking utensils, characterized in that the method comprises the following steps:

[0527] a) providing a disc-shaped metal support having two opposing surfaces;

[0528] b) the step of shaping the carrier so as to have a cap shape comprising a bottom and side walls extending from the bottom and thereby defining a concave inner surface and a convex outer surface suitable for receiving food;

[0529] c) optionally, a step of treating the inner surface of the support to obtain a treated surface that promotes adhesion of the hard bottom on the support;

[0530] d) a step of preparing an adhered hard bottom on the inner face of the carrier;

[0531] e) a step of producing a coating on the hard bottom formed in step d);

[0532] The method is characterized in that step d) of producing the hard bottom comprises thermally spraying a ceramic and / or polymer material in powder form on the inner face to form at least a discontinuous layer on the inner face of the cap, the discontinuous portion being in the form of a partially melted and crystallized surface dispersion substantially uniformly distributed on the inner face, and step b) of shaping the carrier is carried out before step d) of producing the hard bottom or after step e) of producing the ceramic coating.

[0533] The silicone coating consisting of layers (3b), (3b') and (3c) is applied to the macroporous substrate (3a) as follows

[0534] Finally, the composite PEEK / silicone coating was cured at 250 °C for 45 min.

[0535] Example 2: Porous PEEK polymer substrate with silicon carbide and silicone on aluminum

[0536] Process:

[0537] -raw material

[0538] PEEK (polyetheretherketone) is sold under the trade name VICTREX VICOTE 703 is manufactured and sold, with a diameter of D5025 μm, a glass transition temperature of 143°C and a melting temperature of 343°C.

[0539] Silicon carbide (trade name SIKA ABR I F500), diameter D50 = 12.8 μm

[0540] - Equipment: flame blowtorch, Eutectic-Castodyn Castodyn DS8000, reference flame nozzle Eutectic-Castodyn module SSMA40.

[0541] - The moving speed of the blowtorch is 150mm / s to 200mm / s

[0542] -Dual powder feeder, Sulzer Metco, and powder mix flow: variable from 2 to 7 g / min

[0543] -Thickness of the bottom layer: between 10 and 50 μm

[0544] - Propellant gas: Compressed air

[0545] - Fuel gas: 10 to 16 l / min of acetylene, 0.5 to 1 bar of acetylene

[0546] -Fuel gas: oxygen varied from 10 to 20.0 l / min, oxygen pressure varied from 3 to 5 bar

[0547] - Temperature of the carrier during application of the hard base: greater than or equal to ambient temperature (of the order of 20 to 250° C.)

[0548] - Application distance from the blowtorch to the workpiece, between 10 and 20 cm

[0549] - Workpiece rotation speed, between 400 and 800 rpm

[0550] The PEEK / SiC ratio is 70 / 30.

[0551] The silicone coating consisting of layers (3b), (3b') and (3c) was then prepared and applied in the same manner as in Example 1.

[0552] Figure 7 :

[0553] The average size of the equivalent diameter of the pores of the hard underlayer was 14.9 μm (measured by X-ray microtomography within 43 μm from the metal surface).

[0554] Example 3: Porous PEEK polymer base layer with silicon carbide / cold spray method

[0555] The cold spray method is able to obtain thick uniform solid deposits on the surface of the substrate to be coated. The principle of cold spraying lies in the high-speed spraying of powder particles, which will be physically deformed when they collide with the substrate. The pressurized air flow (0.1 to 5MPa) is heated (from 25°C to 1000°C) and then injected into a Laval type convergent-diffuser tube. In this tube, which is called a nozzle, the gas is accelerated until it reaches supersonic speed. The powder is injected into the air flow upstream or downstream of the nozzle. The air flow carries the powder particles to the substrate at high speed. If their kinetic energy is sufficient, the particles as well as the substrate will deform under impact. In the case of deformation, the particles will adhere to the substrate by mechanical bonding and, depending on their properties, by chemical or metallurgical bonding. Subsequent particles will accumulate on the previous layer, forming a more or less thick deposit. The sprayed particles remain solid.

[0556] Equipment description of spraying device:

[0557] The cold sprayer used was CGT Dynamics 3000, connected to a PF4000 powder dispenser. The pressure range was 1 to 3 MPa, and the temperature range was 300 to 500°C.

[0558] The gas used was nitrogen. The spray was carried out using a tungsten carbide "MOC24" nozzle with a diameter of <1 mm, which was attached vertically to the sample and kept 80 mm from the substrate. The irradiation speed was 300 mm.s -1 , the maintenance step length is 1mm.

[0559] For thickness 45 / 10 th The aluminum cap is degreased and then shot-peened or sand-blasted before a surface treatment suitable for removing organic contaminants. The roughness has an Ra of the order of 5 μm, the surface state having been described above. The disk is preheated to a maximum temperature of 260° C. and used to apply a mixture of PEEK and silicon carbide powders (70 / 30 mass ratio) by cold spraying (cold gas dynamic spraying).

[0560] PEEK (polyetheretherketone) is sold under the trademark VICTREX VICOTE 703 manufactured and sold, volume-based diameter D50 = 25 μm.

[0561] A thermal method by cold spraying is used to obtain a discontinuous deposition of the above-mentioned powder and to deposit a layer thickness of the order of 50 μm.

[0562] The silicone coating consisting of layers (3b), (3b') and (3c) was then prepared and applied in the same manner as in Example 1.

[0563] After a single cure at 250°C for 30 minutes, the coating had a surface that was slightly rough to the touch but not cracked.

[0564] Obtaining layers (3b), (3b') and (3c):

[0565] Middle layer (3b)

[0566] Then, one of the successive layers (3b) of Examples 1, 2 and 3 is deposited on layer (3a) by spraying, the successive layers being selected from the layer compositions described below: layer 3b1, layer 3b2 and layer 3b3:

[0567]

[0568]

[0569]

[0570]

[0571] The aqueous composition of layer 3b is prepared according to the ball milling principle. As mentioned above, ball milling is carried out in a tank. The sample can be ground in dry form or dispersed in a suitable solvent (for example in water or alcohol or in a solvent). The dispersion can also contain certain additives (for example dispersants or defoamers).

[0572] The thickness of this layer 3b is 10 to 20 μm, preferably 12 to 15 μm.

[0573] Intermediate layer (3b') and finishing layer (3c)

[0574] As described above, the substrate to which the layer 3a and the continuous layer 3b were applied was coated with a multilayer non-stick coating consisting of an intermediate layer 3b' (6-8 μm) and a finishing layer 3c (14-18 μm) dried for 4 minutes at 100° C. After the deposition of the layers, the assembly was finally heated at 250° C. for 30 minutes to 1 hour, i.e. the process included only one curing step.

[0575] The composition of the intermediate layer 3b' is deposited by spraying and is as follows: layer 3b'1 and layer 3b'2:

[0576]

[0577]

[0578]

[0579]

[0580] The composition of the finishing layer 3c is deposited by spraying and is as follows: Layers 3c1 to 3c10:

[0581]

[0582]

[0583]

[0584]

[0585]

[0586]

[0587]

[0588]

[0589]

[0590]

[0591]

[0592]

[0593]

[0594]

[0595] Comparative Example: Silicone without PEEK Primer on Aluminum

[0596] In this comparative example, no polymer primer layer was applied to the sandblasted aluminum substrate, but instead the same silicone layer as in Examples 1 and 2 was applied directly.

[0597] The method of formulation, coating and final curing also did not change relative to Example 1.

[0598] Test results and SEM / EDXS characterization

[0599] Mechanical shock test

[0600] The results are described below:

[0601]

[0602] Methods for evaluating the performance of non-stick coatings: Egg test performance

[0603] The method for evaluating the performance of non-stick coatings is based on the egg test adapted from paragraph 3.3.2 of standard AFNOR NF D 21-511 and is carried out in the following way:

[0604] Clean the sample and wipe off any water remaining on the surface.

[0605] The inner surface of the container body is dried in advance.

[0606] Heat the cookware on a gas hob to a temperature between 140 and 170°C.

[0607] An egg of size 60 / 65 is broken and then poured into the center of the hot cooking container. Then wait until the egg has set (6 to 9 minutes). The egg is removed from the cooking container with the aid of a spatula and the coating is cleaned with a damp vegetable sponge, by which the non-stick properties of the cooking container are evaluated. Then, the following is recorded:

[0608] Score 100: Use a plastic spatula to completely remove the egg;

[0609] Rating 75: The egg cannot be completely removed but the coating is easily cleaned with a damp sponge.

[0610] Rating 50: The egg cannot be completely removed but is cleaned with a wet sponge.

[0611] Rating 25: The egg could not be completely removed and the coating could not be cleaned with a wet sponge.

[0612] Rating 0: The egg cannot be removed and the coating cannot be cleaned with a wet sponge.

[0613]

[0614] Similar results were obtained without the base layer (3a) according to the comparative example.

[0615] All silicone-polyester resin based coatings of the present invention exhibit good non-stick properties while adhering to metal.

Claims

1. A coated cooking element (1) for a cooking utensil or electric cooking utensil, comprising a metal substrate (2) coated on at least one side (2a) with at least the following layers, in order starting from the metal substrate (2): (3a) a porous hard substrate, which consists of one or more polyether aryl ketones (PEAK) and mixtures thereof, optionally fillers, optionally less than 3 wt. % additives relative to the weight of the hard substrate, and optionally less than 3 wt. % colorants relative to the weight of the hard substrate, (3b) optionally one or more intermediate layers, said intermediate layers consisting of one or more colorants and optionally: - one or more silicone resins, and / or - one or more thermoplastic polymers, and / or - one or more fillers, and / or - one or more additives; (3c) a finishing layer, the finishing layer consisting of one or more silicone resins and optionally: - one or more thermoplastic polymers, and / or - one or more fillers, and / or - one or more additives, and / or - Thin flakes.

2. The coated cooking element (1) according to claim 1, characterized in that The average equivalent diameter of the pores in the hard bottom layer (3a) is greater than 5 μm.

3. The coated cooking element (1) according to claim 2, characterized in that The average equivalent diameter of the pores of the hard sublayer (3a) is greater than 8 μm, preferably greater than 10 μm.

4. The coated cooking element (1) according to any one of the preceding claims, characterized in that The median equivalent diameter of the pores of the hard bottom layer (3a) is greater than 6 μm, preferably greater than 7 μm.

5. The coated cooking element (1) according to any one of the preceding claims, characterized in that The hard bottom layer (3a) contains pores having an equivalent diameter of more than 30 μm, and preferably at least 1% by number of the pores in the hard bottom layer (3a) contain pores having an equivalent diameter of more than 30 μm.

6. The coated cooking element (1) according to any one of the preceding claims, characterized in that The average thickness of the hard bottom layer (3a) is greater than 5 μm, preferably greater than 15 μm.

7. The coated cooking element (1) according to any one of the preceding claims, characterized in that The one or more polyether aryl ketones comprise more than 50% by weight, preferably more than 70% by weight of the hard subbing layer (3a).

8. The coated cooking element (1) according to claim 7, characterized in that The one or more polyether aryl ketones account for more than 97% by weight of the hard bottom layer (3a), and the remainder is optionally made up to 100% by additives.

9. The coated cooking element (1) according to any one of the preceding claims, characterized in that The filler accounts for more than 20% by weight, preferably more than 30% by weight of the hard bottom layer (3a).

10. The coated cooking element (1) according to any one of the preceding claims, characterized in that The hard bottom layer (3a) has a surface roughness Ra between 5 μm and 100 μm.

11. The coated cooking element (1) according to any one of the preceding claims, characterized in that The polyether aryl ketone of the hard bottom layer (3a) is PEEK.

12. The coated cooking element (1) according to any one of the preceding claims, characterized in that The one or more silicone resins are selected from the group consisting of methyl silicone and / or phenyl silicone and / or methyl-phenyl silicone resin, methyl silicone-polyester resin (copolymer), phenyl silicone-polyester resin (copolymer), methyl-phenyl silicone-polyester resin (copolymer), silicone-alkyd resin (copolymer), modified silicone resin and mixtures thereof.

13. The coated cooking element (1) according to any one of the preceding claims, characterized in that The one or more fillers are selected from the group consisting of ceramic and / or mineral and / or metal and / or hydrophobic silica and / or diamond particle fillers.

14. The coated cooking element (1) according to any one of the preceding claims, characterized in that The one or more thermoplastic polymers are selected from polyethersulfone (PES), polyphenylene ethersulfone (PPSU), polyamideimide (PAI), polyimide (PI), polyphenylene ether (PPO), polyarylether sulfide (PAS), polyetherimide (PEI), polybenzimidazole (PBI), liquid crystal polymer (LCP), polyphenylene sulfide (PPS), polyaryletherketone (PAEK) and mixtures thereof, wherein polyaryletherketone (PAEK) includes polyetherketone (PEK), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetheretherketoneketone (PEEKK), and polyetherketoneetherketoneketone (PEKEKK).

15. The coated cooking element (1) according to any one of the preceding claims, characterized in that The one or more colorants are selected from the group consisting of thermochromic pigments, heat stable pigments, flakes, preferably holographic flakes, and mixtures thereof.

16. The coated cooking element (1) according to claim 15, characterized in that The one or more thermochromic pigments are selected from Bi2O3, Fe2O3, V2O5, WO3, CeO2, In2O3, Y 1.84 Ca 0.16 Ti 1.84 V 0.16 O 1.84 、AgI、(Bi 1-x A x )(V 1-y M y )O4, where -x is equal to 0 or x is between 0.001 and 0.999, -y is equal to 0 or y is between 0.001 and 0.999, - A and M are selected from nitrogen, phosphorus, alkali metals, alkaline earth metals, transition metals, poor metals, semimetals or lanthanides, -A and M are different from each other.

17. The coated cooking element (1) according to claim 15 or 16, characterized in that The one or more heat stable pigments are selected from the group consisting of: -Titanium Rutile Yellow Pigment, - yellow pigments derived from bismuth, for example selected from stable bismuth vanadates (Py 184 ) - red pigments, for example selected from perylene red, iron oxide, -Bismuth oxyhalide orange pigment (PO 85 ), -Bismuth vanadate orange pigment (PO 86 ) -Tin-Titanium-Zinc Orange Pigment (PO 82 ) -Cerium sulfide orange pigment (PO 75 PO 78 ) -Chrome antimony titanium rutile orange pigment (PBr 24 ) -Zinc Tin Gold Rutile Orange Pigment (Py 216 ) -Zinc tin sulfide niobium oxide orange pigment (Py 227 ) -Niobium tin double oxide orange pigment -Co3(PO4)2 -LiCoPO4 -CoAl2O4 -Cr2O3 -TiO2 -Black Pigment PBk28 (Copper Chromite Black Spinel) - and mixtures thereof.

18. The coated cooking element (1) according to any one of claims 15 to 17, characterized in that The one or more holographic flakes are a mixture of magnetizable particles and non-magnetizable particles.

19. The coated cooking element (1) according to any one of the preceding claims, characterized in that The metal substrate (2) is a substrate made of aluminum, stainless steel or a multi-layer metal substrate.

20. The coated cooking element (1) according to any one of the preceding claims, characterized in that The proportion of the silicone resin in the layer (3) is greater than or equal to 20% by weight relative to the total weight of the layer (3).

21. The coated cooking element (1) according to any one of the preceding claims, characterized in that The layer (3c) comprises one or more thermoplastic polymers, the proportion of thermoplastic polymers in the layer (3c) being less than 50%, preferably less than 40%.

22. The coated cooking element (1) according to any one of the preceding claims, characterized in that The proportion of fillers in the layer (3a) is greater than 20% by weight, preferably greater than 30% by weight, relative to the total weight of the layer.

23. The coated cooking element (1) according to any one of the preceding claims, characterized in that The proportion of fillers in the layer (3c) is less than 10% by weight, relative to the total weight of the layer.

24. A method for manufacturing a coated cooking element (1) according to any one of the preceding claims, comprising the steps of: a) providing a metal support (2) comprising two opposing surfaces; b) optionally, a step of treating the face (2a) of the support (2) to obtain a treated face (2a) that promotes the adhesion of the hard bottom layer (3a) on the support (2); c) a step of producing an adherent hard base layer (3a) on said inner face (2a) by thermally spraying onto said inner face (2a) a powder or dispersion of one or more polyether aryl ketones (PEAK) and mixtures thereof, optionally fillers, optionally less than 3% by weight of additives relative to the weight of said hard base layer (3a) and optionally less than 3% by weight of colorants; d) optionally drying and / or curing; e) optionally applying the one or more layers (3ab) and / or one or more intermediate layers (3b); f) applying the finishing layer (3c); g) drying and / or curing.

25. A cooking appliance (100) comprising a cooking element (1) according to any one of claims 1 to 23.

26. The cooking utensil (100) according to claim 25, characterized in that: The cooking utensil comprises a heating surface (6) for being placed in contact with an external heating source, the heating surface (6) being opposite to a cooking surface (5) for being placed in contact with food during cooking.

27. The cooking utensil (100) according to claim 25 or 26, which is selected from the group consisting of a frying pan, a frying pan, a pot or pot for cheese fondue or raclette, a stew pot, a wok, a frying pan, a pancake maker, a grill, a frying pan, a casserole, a container for a cooker or a bread maker, and a cooking mold.

28. An electric cooker (200) comprising a coated cooking element (1) and a heating source (210) configured to heat the coated cooking element (1), characterized in that: The coated cooking element (1) is a cooking element according to any one of claims 1 to 23.

29. The electric cooking appliance (200) according to claim 28, which is selected from the group consisting of an electric pancake maker, an electric raclette maker, an electric fondue maker, an electric grill, an electric frying pan, an electric rice cooker, a bread maker or an electric pressure cooker, a waffle maker, an electric rice cooker and a jam maker.

Citation Information

Patent Citations

  • Sol-gel coating comprising anisotropic particles and a culinary article provided with such a coating

    EP2806776B1

  • Fluorine free anti-stick coating and method for its production

    US20220073785A1

  • Anti-adhesive coating

    WO2020144051A1